Predictors of Initial and Sustained Remission in Patients Treated with Antithyroid Drugs for Graves' Hyperthyroidism: The RISG Study. (3rd January 2019) - Karmisholt, J.; Andersen, S. L.; Bulow-Pedersen, I.; Carlé, A.; Krejbjerg, A.; Nygaard, B.
Abstract : Purpose. To study predictors of attaining (part 1) and sustaining (part 2) remission in patients with Graves' hyperthyroidism (GH) treated with antithyroid drugs (ATD). Methods. In the prospective first part, the included patients were treated with ATD until a prespecified definition of remission (thyrotropin > 0.4 mU/L and TSH-receptor antibodies (TRAb) ≤ 1. 0 IU/L in a patient receiving a methimazole dose ≤ 5 mg/day, on two occasions two months apart) was met, or for 24 months. In the second part, patients attaining remission in part 1 were randomized to treatment or observation and followed until relapse or for 24 months. Results. 173 patients completed study 1 and 53% attained remission. TRAb and age were the only significant predictors of remission. Patients with baseline TRAb below vs above 10 IU/L attained remission in 63% compared to 39%, and 5 months priorly (p<0.001). In study 2, 96.4% of the patients randomized to treatment (n=33) sustained remission compared to 66% in the observation group (n=33). Treatment arm was the only significant parameter (p<0.001) of sustained remission. Conclusion. Baseline TRAb was prognostic for attaining remission in GH. Consecutive TRAb measurements during treatment were not worthwhile, but a single measurement after 6-8 months in patients with initial TRAb < 10 IU/L could substantially shorten the treatment period in a subgroup of patients. Only 3.6% of the patients in remission experienced relapse during follow-up when treated with a combination of fixed low dose methimazole and L-T4.ClinTrial.gov registration number is   NCT00796913 .